Electromagnetic compatibility (EMC). Testing and measurement techniques. Testing and measurement techniques. Voltage dips, short interruptions and voltage variations on d.c. input power port immunity tests Part 4-29, (15th July 2001) - British Standards Institution,
No abstract available